Functional and nutraceutical properties of pumpkin – a review. Issue 2 (12th August 2019) - Kaur, Simran; Panghal, Anil; Garg, M.K.; Mann, Sandeep; Khatkar, Sunil K.; Sharma, Poorva; Chhikara, Navnidhi
Abstract : Purpose: The purpose of this paper is to review the nutritional and food value of pumpkin Cucurbita, along with different health benefits. Cucurbita (pumpkin) is an herbaceous vine, member of Cucurbitaceae family. It is an edible, heat-sensitive plant, which has an abundant amount of active compounds such as carotenoids, alkaloids, flavonoids, polyphenols, tannins, tocopherols, phytosterols and cucurbitacin, accounted for numerous health benefits, namely, antidiabetic, antioxidant, anticarcinogenic, hypotensive, hyper protective activities. Design/methodology/approach: Major well-known bibliometric information sources such as Web of Science, Scopus, Mendeley and Google Scholar were searched with keywords such as nutrition value of Cucurbita, Cucurbita utilization, bioactive compounds of pumpkin, health benefits, processing, food formulations and current scenarios were chosen to obtain a large range of papers to be analyzed. A final inventory of 105 scientific sources was made after sorting and classifying them according to different criteria based on topic, academic field, country of origin and year of publication. Findings: The comprehensive review of different literature, data sources and research papers seeks to find and discuss various nutritional benefits of pumpkin. It contains all necessary macro- and micro-nutrients, amino acids, vitamins, antioxidants and bioactive compounds with a relatively low amount of antinutrients. The recent upsurge in consumer interest for health-promoting products has opened up new vistas for plant products containing bioactive compounds in different food formulations. Originality/value: This paper contains information regarding the chemical composition, nutritive value, phytochemical studies, pharmacological properties, bio-accessibility, food and industrial applications of pumpkin. Worldwide, pumpkin is used as food additive in various food products such as candy, weaning mix, corn grits, kheer, jam, crackers, bread, etc. Effect of different processing methods such as high temperature, pH, blanching, oven drying, freeze-drying to retain or minimize its losses in case of color, texture, flavor, and the carotenoids are of concern. The review paper highlights the nutritional, therapeutic, potential and processing attributes.